2022
DOI: 10.1002/smll.202201680
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplastic Toxicity: Insights and Challenges from Experimental Model Systems

Abstract: Nanoplastic particles (NPs) can be produced or derived from the degradation of several daily used products and can therefore be found in the air, water, and food. Every day, these microscopic particles are confronted by different routes of exposure. Recent investigations have shown the internalization of these particles, differing in size and modification, in vivo in aquatic organisms and terrestrial organisms, as well as in vitro in different human cell lines. During the last years, the number of studies inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 169 publications
1
17
0
Order By: Relevance
“…53 It is important to highlight that internalization represents the initial event that can lead to adverse outcomes associated with nanoparticles. 7,20,53 Endocytosed NPs (regardless of surface charge) were observed to progressively aggregate within lysosomes (Figure 5b and Figure S7a), a major accumulation organelle for nanoparticles. 24,54,55 These aggregations led to lysosomal swelling, significantly increasing lysosomal membrane permeability with a more pronounced effect being observed in p-NP treatments (Figure 5c).…”
Section: Integrating Proteomics and Transcriptomics Analysis To Unrav...mentioning
confidence: 99%
“…53 It is important to highlight that internalization represents the initial event that can lead to adverse outcomes associated with nanoparticles. 7,20,53 Endocytosed NPs (regardless of surface charge) were observed to progressively aggregate within lysosomes (Figure 5b and Figure S7a), a major accumulation organelle for nanoparticles. 24,54,55 These aggregations led to lysosomal swelling, significantly increasing lysosomal membrane permeability with a more pronounced effect being observed in p-NP treatments (Figure 5c).…”
Section: Integrating Proteomics and Transcriptomics Analysis To Unrav...mentioning
confidence: 99%
“…[ 1–4 ] Common polymers found as MPs are polyethylene (PE), polystyrene (PS), and polymethylmethacrylate. MPs are potential carriers of toxic organic and heavy metal components, are ingested by marine animals and fish [ 2,5–12,26 ] and end up localized in their guts, and are also known to penetrate human tissues more easily than larger particles. [ 13–15 ] While the health risks and environmental consequences of microplastics appear potentially significant, capture and identification of MPs in the environment is an unresolved challenge due to their heterogeneity in chemical composition, shape and size.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Common polymers found as MPs are polyethylene (PE), polystyrene (PS), and polymethylmethacrylate. MPs are potential carriers of toxic organic and heavy metal components, are ingested by marine animals and fish [2,[5][6][7][8][9][10][11][12]26] and…”
mentioning
confidence: 99%
“…Global plastic pollution and the detection of micro- and nanoplastic particles in almost all environmental compartments and geographic regions has fuelled research into the possible effects of these particles on environmental organisms. One specific research question is whether nanoplastic particles exert specific and/or enhanced effects in organisms in comparison to microplastics [ 1 , 2 , 3 , 4 ]. However, studies have reported different conclusions regarding this question.…”
Section: Introductionmentioning
confidence: 99%